2021
DOI: 10.3389/fmicb.2021.610859
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Aza-Derivative Inhibits agr Quorum Sensing Signaling and Synergizes Methicillin-Resistant Staphylococcus aureus to Clindamycin

Abstract: Increasing antibiotic resistance and diminishing pharmaceutical industry investments have increased the need for molecules that can treat infections caused by dangerous pathogens such as methicillin-resistant Staphylococcus aureus (MRSA). Quorum Sensing (QS) is a signaling mechanism that regulates bacterial virulence in pathogens. A report demonstrating that the anti-inflammatory drug Diflunisal reduces MRSA virulence factors’ expression prompted us to design, synthesize and test 16 aza-analogs as inhibitors o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…Additionally, Abbas et al showed that diclofenac had a signi cant down-regulation effect on the relative expression of virulence regulating genes SarA, AgrA, hla, FnbA, IcaA, SigB, and CrtM in S. aureus [63]. In another study, parallel with the current results, azan-7 (a novel aza-derivative) signi cantly reduced hla and agrA gene expression in MRSA [73]. Moreover, in accordance with our results, luteolin (a avonoid of plant origin), and alpha-cyperone (a Chinese medicinal herb) inhibit hla and agrA gene expression in S. aureus [74].…”
Section: Discussionsupporting
confidence: 80%
“…Additionally, Abbas et al showed that diclofenac had a signi cant down-regulation effect on the relative expression of virulence regulating genes SarA, AgrA, hla, FnbA, IcaA, SigB, and CrtM in S. aureus [63]. In another study, parallel with the current results, azan-7 (a novel aza-derivative) signi cantly reduced hla and agrA gene expression in MRSA [73]. Moreover, in accordance with our results, luteolin (a avonoid of plant origin), and alpha-cyperone (a Chinese medicinal herb) inhibit hla and agrA gene expression in S. aureus [74].…”
Section: Discussionsupporting
confidence: 80%
“…PAO1 was cultured in LB with DMSO or supplemented with the selected molecules for 24 h at 37°C. Then cultures were centrifuged, the medium discarded and total RNA was isolated and purified using the GRS Total RNA Kit—Bacteria (#GK16.0100, GRISP Research Solution) with mechanical and enzymatic cellular disruption, according to the manufacturer’s instructions and as previously described ( Berbabè et al, 2021 ). A treatment with DNase I was used to remove contaminating DNA.…”
Section: Methodsmentioning
confidence: 99%
“…The distance movement was calculated using the freely available software ImageJ. Plates inoculated with not-treated PAO1 were used as the positive control ( Berbabè et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The a ccessory g ene r egulator ( agr ) quorum-sensing system, a globe transcriptional regulator of Staphylococcus aureus , plays a key role in its pathogenesis and resistance ( Bernabè et al, 2021 ) and has been intensively studied to aid drug and vaccine development ( Tan et al, 2018 ). The agr locus comprises two adjacent transcripts, RNAII and RNAIII, which are controlled by P2 and P3 promoters, respectively ( Ji et al, 1995 ).…”
Section: Introductionmentioning
confidence: 99%